Riding the blockchain mania: Public firms’ speculative 8-K disclosures - LIN, Pengkai (Institutional Knowledge at Singapore Management University, 2019)
This paper provides evidence on public firms' initial 8-K disclosures that mention Blockchain and investors' response to these disclosures. We categorize the description of Blockchain activities in firms' 8-Ks as Speculative (e.g., a vague future plan that involves Blockchain) or Existing (e.g., a description of Blockchain product). We document a sharp increase in the number of initial 8-K disclosures of Blockchain, particularly by Speculative firms, coinciding with the rise of Bitcoin prices and excitement in Blockchain technology in the last quarter of 2017. Investors react positively to the Blockchain 8-Ks issued by Speculative firms in the initial seven-day event window although the reaction is mostly reversed over the 30 days following the disclosure. The reaction is stronger when Bitcoin returns are more positive. Overall, our results are consistent with a situation that troubles the SEC and the financial press: investors overreact to a firm's first 8-K disclosure of a potential foray into Blockchain technology and that overreaction is a function of the Bitcoin price bubble.